Trophic structure of key taxa in rocky intertidal communities in two contrasting high-latitude environments. (April 2022) - Siegert, Danielle; Konar, Brenda; Lindeberg, Mandy R.; Saupe, Susan; Iken, Katrin
Abstract: Coastal ecosystems in high latitudes are increasingly impacted by glacial melt and river discharge due to climate change. One way to understand ecosystem responses to these stressors is assessing trophic relationships. The goal of this study was to better understand how hydrography influences trophic structure in high-latitude rocky intertidal systems. Our working hypothesis was that food web structure differs based on hydrographic conditions. We compared the trophic structure of key taxa in two rocky intertidal assemblages in the northwestern Gulf of Alaska with a similar regional species pool, but differing hydrological inputs: one glacially influenced and one primarily marine influenced. Common macroalgal and invertebrate taxa, as well as particulate organic matter (POM) were sampled at three rocky intertidal sites in each region in 2017 and 2018. Food web structure was compared using trophic metrics based on the distribution of shared taxa in isotopically-derived (δ 13 C and δ 15 N) trophic niche space. The trophic niche space of the select taxa in the glacially-influenced rocky intertidal system was larger, driven by larger ranges in both carbon and nitrogen stable isotope values. Lower δ 13 C and δ 15 N values in POM in this system suggest that diverse glacially-influenced allochthonous organic material was incorporated into the food web. Macroalgae were a more important food source than POM in both regions, and even more so in the glacially-influenced region, where macroalgae may be an energetically preferable food source compared to silt-laden glacial inputs. This study suggests that common intertidal taxa have high trophic flexibility enabling them to respond to variable food sources under differing environmental conditions, especially by broadening resource use in more stressful (glacial) conditions. This supported another of our hypotheses, i.e. that taxa in food webs occupying a larger trophic niche space engaged in more heterogeneous trophic pathways and used more diverse resources, which tends to make such systems more stable to perturbations that could affect a single resource. The common taxa of high-latitude rocky intertidal systems studied here seem to be able to respond to the current stress levels of glacial input by using more diverse resources. However, it remains to be seen how well these systems are suited to maintain trophic stability with an expected increase in glacial stress from climate warming.